Utilization of Polysaccharides Extracted from Tofu Processing Wastewater for Microencapsulation Processes in the Food Industry: Experimental Investigation - T. S. Sonda; Memuna K. Sawi; Abigail Nyamawa; M. S. Sonda (Research Highlights in Agricultural Sciences Vol. 6, 2022)
The purpose of this research was to extract polysaccharides from tofu processing wastewater obtained from tofu factory located at the outcast of Wuxi city, PR China. The food sector employed the extracted polysaccharide as a wall material for microencapsulation procedures. Due to the fact that wastewater is transformed into beneficial polysaccharides that might be used in the food industry, this research strategy is anticipated to be ecologically friendly. Vegetable oil was the main component of this study, which served as a test case to see whether a successful encapsulation process could be accomplished, indicating the potential for the encapsulation of oil-soluble vitamins and minerals. A successful production of microcapsules using the extracted polysaccharides will serve as a cheap source of obtaining wall materials for encapsulation processes. Polysaccharides extracted from tofu processing wastewater were employed as wall materials for vegetable fat load encapsulation. The fundamental approach used in the microencapsulation process is that, upon the addition of polysaccharides, the interfacial coacervation between the protein and the polysaccharide surrounding the oil droplets drives the production of microcapsules. On spray-dried microcapsules, the peroxide value, microencapsulation effectiveness, and visual observation were investigated. In order to create self-sustaining entities or microcapsules, the coating was thermally solidified to create microencapsulated capsules. To vividly display the microcapsules, photomicrographs were used. The microcapsules’ microencapsulation efficiency was investigated, and the findings indicate that the maximum MEE (93.04%) was attained with a comparably low vegetable fat content. This demonstrates a correlation between the percent fat load and MEE: the lower the microencapsulation efficiency, the higher the percentage fat load of vegetables. Studies on the peroxide content of the microcapsules revealed a reduced shelf-life at increased temperatures of 38ºC in comparison to room temperature.